Relationship Marketing: A Perspective for Marketing Success (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Tho article tracos out the evolution of relationship with  marketing and discuss Its Importance In today's highly  turbulent marketing environment. The thoughts of various  management thinkers on relationship marketing  approach have been also incorporated along with an  overview on the implementation of Relationship  Marketing In the organization. The article envisages  relat,onshlp marketing as a recipe for marketing in the  organization. The article envisages relationship  marketing as a recipe for marketing success.
Keywords: Relaflonship Marketing; Marketing Mix; Transaction Marketing; Customer Relationship